The Kaiju Preservation Society [large type] - Scalzi, John, 1969- (Thorndike Press, a part of Gale, a Cengage Company, 2022)
"The Kaiju Preservation Society is John Scalzi's first standalone adventure since the conclusion of his New York Times bestselling Interdependency trilogy. When COVID-19 sweeps through New York City, Jamie Gray is stuck as a dead-end driver for food delivery apps. That is, until Jamie makes a delivery to an old acquaintance, Tom, who works at what he calls "an animal rights organization." Tom's team needs a last-minute grunt to handle things on their next field visit. Jamie, eager to do anything, immediately signs on. What Tom doesn't tell Jamie is that the animals his team cares for are not here on Earth. Not our Earth, at least. In an alternate dimension, massive dinosaur-like creatures named Kaiju roam a warm and human-free world. They're the universe's largest and most dangerous panda and they're in trouble. It's not just the Kaiju Preservation Society who have found their way to the alternate world. Others have, too. And their carelessness could cause millions back on our Earth to die"--